# How do you find the inverse of a function of a function?

Table of Contents

## How do you find the inverse of a function of a function?

Finding the Inverse of a Function

- First, replace f(x) with y .
- Replace every x with a y and replace every y with an x .
- Solve the equation from Step 2 for y .
- Replace y with f−1(x) f − 1 ( x ) .
- Verify your work by checking that (f∘f−1)(x)=x ( f ∘ f − 1 ) ( x ) = x and (f−1∘f)(x)=x ( f − 1 ∘ f ) ( x ) = x are both true.

**Which is the inverse of the function?**

The inverse of a function can be viewed as reflecting the original function over the line y = x. In simple words, the inverse function is obtained by swapping the (x, y) of the original function to (y, x).

**Which equation is the inverse of Y 2×2 8 quizlet?**

Answer: √[(x + 8) / 2] is the inverse of y = 2×2 – 8.

### Which equation is the inverse of Y 3x?

Answer: The Inverse of y = 3x is f-1(x) = 1/3x.

**Is the inverse of a function always a function?**

The inverse is not a function: A function’s inverse may not always be a function. Therefore, the inverse would include the points: (1,−1) and (1,1) which the input value repeats, and therefore is not a function. For f(x)=√x f ( x ) = x to be a function, it must be defined as positive.

**Which equation is the inverse of Y 2×2 8?\?**

## Which equation is the inverse of Y 2×2?

Answer: The inverse of the function y = 2×2 + 2 is f-1(x) = √(x – 2) / √2.

**What is the inverse function of y 2x 3?**

Answer : f-1(x) = (x – 3) / 2. Let’s see how we will use the concept of transposition to find the inverse function. For finding inverse we will solve y = 2x + 3 to write x as a function of y and that will be our inverse function.

**What is the inverse of 3x 4?**

The inverse function of 3x – 4 is (x+4)/3.

### What is the inverse of a exponent?

Logarithmic functions are the inverses of exponential functions. The inverse of the exponential function y = ax is x = ay. The logarithmic function y = logax is defined to be equivalent to the exponential equation x = ay.

**What is the inverse of Y=log base 3 of X?**

The inverse of y=log base 3 of x is found by interchanging x and y, then solving for y. Switching gives us x=log base 3 of y. So y=3^x is the inverse. The inverse of log (3x)=y: Interchanging, we have log (3y)=x. So 10^x=3y, hence the inverse would be y= (1/3)•10^x Why does?

**How do you find the inverse of a logarithmic function?**

In finding the inverse of the given logarithmic function f, we must first interchange the x and y variables in the given equation defining function f as follows: (1.) y = log 3x, which is equivalent to 10ʸ = 3x, becomes: (2.) x = log 3y, since the ordered pairs between the two functions, f and f ̄¹, are re…

## How do you convert logarithmic equations to exponential equations?

STEP 1: Replace the function notation f (x) by y. STEP 2: Switch the roles of x and y. STEP 3: Isolate the log expression on one side (left or right) of the equation. STEP 4: Convert or transform the log equation into its equivalent exponential equation.

**What is the meaning of the inverse?**

The inverse of [math]log(x)math] is raising the base to the power of the logarithm. For example, the inverse of [math]log(2)[/math] is [math]10[/math] ^ [math]log(2)[/math] Back to our problem. This means that we take the base, and raise it to the power of both sides.